Coated glass free of chromatic aberration and high in adhesive force and preparation method of coated glass

By using a combination technology of boric acid metal bonding layer and nano zinc oxide thin film layer in coated glass, the color difference and adhesion problems of coated glass are solved, and the effect of colorless difference and strong adhesion is achieved, which improves the aesthetics of the building and Durability.

CN119118528APending Publication Date: 2024-12-13HEJIAN XINYI GLASS PRODUCTS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411015418.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

There are problems of color difference and insufficient adhesion during the preparation process of existing coated glass, which affects the aesthetics and service life of the building.

Method used

Using the combination technology of boric acid metal bonding layer and nano zinc oxide film layer, a borate film with a B-O-B three-dimensional network structure is formed through the impregnation and lifting process, and partially recombined with the nano zinc oxide to form a composite film layer to improve adhesion and Self-cleaning performance.

Benefits of technology

The coating glass without color difference is achieved, which significantly improves adhesion and self-cleaning performance, ensuring the durability and aesthetics of the glass.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses chromatic aberration-free high-adhesion coated glass and a preparation method thereof, and relates to the technical field of glass. The preparation method comprises the following steps: immersing base glass into a borate solution by using a pulling dipping method, forming a bonding layer on one side of the glass, forming a borate film with a B-O-B three-dimensional network structure by a BOH group in a boric acid metal hydrolysate and the surface of the glass, immersing the glass into zinc oxide sol, and carrying out pulling dipping secondary coating to form a nano zinc oxide film. The double-layer film is partially compounded with the boric acid metal layer, so that the double-layer film has the characteristics of a composite film and has a microporous structure, the bonding force between the two layers of films is effectively improved, and the glass film has strong adhesive force, good light transmission of metal ions, no color difference of the glass, strong catalytic property and self-cleaning property. The glass prepared by the invention has the effects of no color difference, self-cleaning and strong adhesive force.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass, in particular to a coated glass with no color difference and strong adhesion. Background Art

[0002] With the rapid development of the modern construction industry and the increasing requirements for architectural aesthetics, coated glass, as a high-performance building material, has been widely used in building curtain walls. Coated glass can not only provide good energy-saving effects, but also effectively block ultraviolet rays, reduce the fading of indoor furniture and decorations, and has certain privacy protection and sound insulation functions. In addition, its unique optical effect also provides more possibilities for architectural exterior design.

[0003] However, there are some technical difficulties in the preparation process of existing coated glass. Among them, one of the most significant problems is color difference. Color difference not only affects the overall aesthetics of the building, but may also cause visual discomfort. Another key issue is the adhesion of coated glass. Due to various factors, such as the selection of coating materials, preparation process, environmental conditions, etc., the coating of coated glass may fall off, which not only affects the service life of the glass, but also may bring safety hazards.

[0004] Therefore, the market is in urgent need of a coated glass that can effectively solve the color difference problem and has strong adhesion. The research and development of this new type of coated glass will be able to better meet the high standards of modern architecture for combining beauty, durability and functionality. Summary of the invention

[0005] The object of the present invention is to provide a coated glass with no color difference and strong adhesion, so as to solve the problems existing in the prior art.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: a color-free and highly-adhesive coated glass, wherein the color-free and highly-adhesive coated glass comprises a glass base layer, a boric acid metal bonding layer, and a nano-thin film layer.

[0007] Furthermore, the glass substrate is tempered glass with a thickness of 4 to 10 mm.

[0008] Furthermore, the metal thickness of the borate metal bonding layer is 4 to 8 μm.

[0009] Furthermore, the nano film layer is composed of nano zinc oxide and has a thickness of 3 to 6 μm.

[0010] Furthermore, a method for preparing coated glass without color difference and with strong adhesion comprises the following preparation steps:

[0011] (1) washing and drying the glass substrate, immersing it in a boric acid metal hydrolyzate solution for 3 hours, pulling it up at a constant speed of 60 to 120 mm / s, and drying it at 60 to 75° C. for 60 to 120 minutes, thereby obtaining a boric acid metal bonding layer glass;

[0012] (2) immersing the borate metal bonding layer glass sheet obtained above in zinc oxide sol for 1 minute, and pulling the glass substrate with a pulling machine at a pulling speed of 5 mm / s. After the wet film on the surface of the glass substrate is dried in air for 2 minutes, the above operation is repeated until the desired thickness is reached;

[0013] (3) The obtained wet film was dried at room temperature, and then dried in a constant temperature drying oven for 0.5 h, with the temperature set at 70-90 °C. Finally, the dried film sample was placed in a muffle furnace, and the temperature was raised to 550 °C at a rate of 1 °C / min. It was kept at 550 °C for 2 h, and then taken out after natural cooling to obtain a zinc oxide nanofilm with a thickness of 3-6 μm.

[0014] Furthermore, the concentration of the metal borate salt in the metal borate hydrolysis solution is 30%, and the metal borate salt is chromium borate.

[0015] Furthermore, the molar ratio of zinc in the zinc oxide sol to non-boron metal ions in the borate metal hydrolysis solution is 5:1.

[0016] Furthermore, the zinc oxide sol is prepared from zinc acetate as a raw material and polyvinyl alcohol with a molecular weight of 10,000 as an organic solvent, with a mass ratio of 1:10.

[0017] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0018] The present invention uses a borate solution and an immersion and pulling process to prepare a borate metal layer coating. The BOH groups in the borate metal hydrolyzate form a borate film with a BOB three-dimensional network structure on the glass surface, which greatly improves the adhesion between the borate metal bonding layer and the glass, and further composites with the nanostructure on the other side to form a composite thin film layer.

[0019] The secondary coating of the present invention uses nano zinc oxide material, and the borate metal layer is partially compounded with the nano zinc oxide, so that the double-layer film has the characteristics of a composite film and a microporous structure appears. The borate metal layer improves the roughness of the end face, which is convenient for increasing the micropores of the nano zinc oxide, effectively improving the bonding force between the two film layers, and making the glass film have strong adhesion.

[0020] The borate metal layer of the present invention is partially compounded with nano zinc oxide, and the metal ions can improve the visible light transmittance of the zinc dioxide self-cleaning film layer, so that the glass has no obvious color difference, and the photocatalytic efficiency of zinc dioxide is increased to about 30%, thereby improving its catalytic performance, being able to fully decompose various organic substances, and making the glass self-cleaning. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0022] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of a coating film without color difference and strong adhesion prepared in the following examples are as follows:

[0023] Adhesion: GB / T1720-1988

[0024] Self-cleaning property: The hydrophilic effect of the embodiment and the comparative example of the same size was tested, and the surface hydrophilic contact angle was measured with a contact angle meter. The volume of the water droplet was 1 μL, and each sample was measured 5 times and the average value was taken.

[0025] No color difference: Take the embodiment and the comparative example of the same thickness and measure the light transmittance of the samples with a spectrophotometer.

[0026] Example 1

[0027] (1) washing and drying a glass substrate with a thickness of 10 mm, immersing it in a boric acid metal hydrolyzate solution for 3 h, pulling it up at a constant speed of 120 mm / s, and drying it at 75° C. for 120 min, thereby obtaining a boric acid metal bonding layer glass, wherein the boric acid metal bonding layer has a thickness of 48 μm; the boric acid metal salt concentration in the boric acid metal hydrolyzate solution is 30%, and the boric acid metal salt is chromium borate;

[0028] (2) immersing the borate metal bonding layer glass obtained above in zinc oxide sol for 1 minute, wherein the molar ratio of zinc in the zinc oxide sol to the non-boron metal ions in the borate metal hydrolysis solution is 5:1, and pulling the glass substrate with a pulling machine, and the pulling speed is set to 5 mm / s. After the wet film on the surface of the glass substrate is dried in air for 2 minutes, the above operation is repeated until the desired thickness is reached; the zinc oxide sol is prepared from zinc acetate as a raw material and polyvinyl alcohol with a molecular weight of 10,000 as an organic solvent, and the mass ratio is 1:10;

[0029] (3) The obtained wet film was dried at room temperature and then dried in a constant temperature drying oven for 0.5 h at 90 °C. Finally, the dried film sample was placed in a muffle furnace and the temperature was raised to 550 °C at a rate of 1 °C / min. The temperature was kept at 550 °C for 2 h and taken out after natural cooling to obtain a zinc oxide nanofilm with a thickness of 6 μm.

[0030] Example 2

[0031] (1) washing and drying a glass substrate with a thickness of 4 mm, immersing it in a boric acid metal hydrolyzate solution for 3 h, pulling it up at a constant speed of 60 mm / s, and drying it at 60° C. for 60 min, thereby obtaining a boric acid metal bonding layer glass, wherein the boric acid metal bonding layer has a thickness of 4 μm; the boric acid metal salt concentration in the boric acid metal hydrolyzate solution is 30%, and the boric acid metal salt is chromium borate;

[0032] (2) immersing the borate metal bonding layer glass obtained above in zinc oxide sol for 1 minute, wherein the molar ratio of zinc in the zinc oxide sol to the non-boron metal ions in the borate metal hydrolysis solution is 5:1, and pulling the glass substrate with a pulling machine, and the pulling speed is set to 5 mm / s. After the wet film on the surface of the glass substrate is dried in air for 2 minutes, the above operation is repeated until the desired thickness is reached; the zinc oxide sol is prepared from zinc acetate as a raw material and polyvinyl alcohol with a molecular weight of 10,000 as an organic solvent, and the mass ratio is 1:10;

[0033] (3) The obtained wet film was dried at room temperature and then dried in a constant temperature drying oven for 0.5 h at 70 °C. Finally, the dried film sample was placed in a muffle furnace and the temperature was raised to 550 °C at a rate of 1 °C / min. The temperature was kept at 550 °C for 2 h and taken out after natural cooling to obtain a zinc oxide nanofilm with a thickness of 3 μm.

[0034] Example 3

[0035] (1) washing and drying a glass substrate with a thickness of 8 mm, immersing it in a boric acid metal hydrolyzate solution for 3 hours, pulling it up at a constant speed of 100 mm / s, and drying it at 68° C. for 100 minutes, thereby obtaining a boric acid metal bonding layer glass, wherein the boric acid metal bonding layer has a thickness of 6 μm; the boric acid metal salt concentration in the boric acid metal hydrolyzate solution is 30%, and the boric acid metal salt is chromium borate;

[0036] (2) immersing the borate metal bonding layer glass obtained above in zinc oxide sol for 1 minute, wherein the molar ratio of zinc in the zinc oxide sol to the non-boron metal ions in the borate metal hydrolysis solution is 5:1, and pulling the glass substrate with a pulling machine, and the pulling speed is set to 5 mm / s. After the wet film on the surface of the glass substrate is dried in air for 2 minutes, the above operation is repeated until the desired thickness is reached; the zinc oxide sol is prepared from zinc acetate as a raw material and polyvinyl alcohol with a molecular weight of 10,000 as an organic solvent, and the mass ratio is 1:10;

[0037] (3) The obtained wet film was dried at room temperature and then dried in a constant temperature drying oven for 0.5 h at 80 °C. Finally, the dried film sample was placed in a muffle furnace and the temperature was raised to 550 °C at a rate of 1 °C / min. The temperature was kept at 550 °C for 2 h and taken out after natural cooling to obtain a zinc oxide nanofilm with a thickness of 4.5 μm.

[0038] Comparative Example 1

[0039] The difference between Comparative Example 1 and Example 1 lies in step (1). Step (1) is changed to washing and drying the glass substrate, immersing it in silane metal liquid, pulling it at a constant speed of 120 mm / s, and drying it at 75°C for 120 minutes, thereby obtaining silanized glass; the other steps are the same as Example 1.

[0040] (1) A glass substrate with a thickness of 10 mm was washed and dried, and immersed in a zinc oxide sol for 1 min, wherein the molar ratio of zinc in the zinc oxide sol to the non-boron metal ions in the borate metal hydrolysis solution was 5:1, and the glass substrate was pulled by a pulling machine, and the pulling speed was set to 5 mm / s. After the wet film on the surface of the glass substrate was dried in air for 2 min, the above operation was repeated until the desired thickness was reached; the zinc oxide sol was prepared from zinc acetate as a raw material and polyvinyl alcohol with a molecular weight of 10,000 as an organic solvent, and the mass ratio was 1:10;

[0041] (2) The obtained wet film was dried at room temperature, and then dried in a constant temperature drying oven for 0.5 h, the temperature was set at 90 °C, and finally the dried film sample was placed in a muffle furnace, the temperature was raised to 550 °C at a rate of 1 °C / min, and kept at 550 °C for 2 h. After natural cooling, it was taken out to obtain a zinc oxide nanofilm with a thickness of 6 μm.

[0042] Comparative Example 2

[0043] (1) washing and drying a glass substrate with a thickness of 10 mm, immersing it in a boric acid metal hydrolyzate solution for 3 h, pulling it up at a constant speed of 120 mm / s, and drying it at 75° C. for 120 min, thereby obtaining a boric acid metal bonding layer glass, wherein the boric acid metal bonding layer has a thickness of 48 μm; the boric acid metal salt concentration in the boric acid metal hydrolyzate solution is 30%, and the boric acid metal salt is chromium borate;

[0044] (2) Place the sample in a muffle furnace and raise the temperature to 550°C at a rate of 1°C / min. Keep the temperature at 550°C for 2 h. Then cool the sample naturally and take it out to obtain glass.

[0045] Effect example

[0046] Table 1 below shows the performance analysis results of a coating film without color difference and with strong adhesion using Examples 1 to 3 of the present invention and Comparative Examples 1 to 2.

[0047] Table 1

[0048] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Adhesion Level 2 Level 1 Level 0 Level 1 Level 0 Light transmittance (%) 94.6 93.7 94.1 88.9 86.7 Hydrophilic contact angle (°) 2.5 2.2 2.1 2.3 18.9

[0049] From the data comparison of the embodiment and the comparative example, it can be found that the present invention first uses the pulling and dipping method to immerse the base glass in the borate solution to form a bonding layer on one side of the glass. The BOH group in the borate metal hydrolyzate forms a borate film with a BOB three-dimensional network structure on the glass surface, and then the glass is immersed in the zinc oxide sol, and the pulling and dipping secondary coating is formed to form a nano zinc oxide film. The borate metal layer and the nano zinc oxide are partially composited, so that the double-layer film has the characteristics of a composite film and a microporous structure appears. The borate metal layer improves the roughness of the end face, which is convenient for the increase of nano zinc oxide micropores, and effectively improves the bonding force between the two layers of film, so that the glass film has strong adhesion. Metal ions can improve the visible light transmittance of the zinc dioxide self-cleaning film layer, so that the glass has no obvious color difference, and the zinc dioxide photocatalytic efficiency is increased to about 30%, which improves its catalytic performance, can fully decompose various organic matter, and make the glass self-cleaning.

[0050] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A coated glass with no color difference and strong adhesion, characterized in that: The color-free and highly adhesive coated glass comprises a glass base layer, a boric acid metal bonding layer, and a nano film layer.

2. The non-color-difference and highly-adhesive coated glass according to claim 1, characterized in that: The glass substrate is tempered glass with a thickness of 4 to 10 mm.

3. The non-color-difference and highly-adhesive coated glass according to claim 1, characterized in that: The metal thickness of the borate metal bonding layer is 4-8 μm.

4. The non-color-difference and highly-adhesive coated glass according to claim 1, characterized in that: The nano film layer is composed of nano zinc oxide and has a thickness of 3 to 6 μm.

5. A method for preparing coated glass with no color difference and strong adhesion, characterized in that: The method comprises the following preparation steps: (1) washing and drying the glass substrate, immersing it in a boric acid metal hydrolyzate solution for 3 hours, pulling it up at a constant speed of 60 to 120 mm / s, and drying it at 60 to 75° C. for 60 to 120 minutes, thereby obtaining a boric acid metal bonding layer glass; (2) immersing the boric acid metal bonding layer glass obtained above in zinc oxide sol for 1 minute, and pulling the glass substrate with a pulling machine at a pulling speed of 5 mm / s. After the wet film on the surface of the glass substrate is dried in air for 2 minutes, the above operation is repeated until the desired thickness is reached; (3) The obtained wet film was dried at room temperature, and then dried in a constant temperature drying oven for 0.5 h, with the temperature set at 70-90 °C. Finally, the dried film sample was placed in a muffle furnace, and the temperature was raised to 550 °C at a rate of 1 °C / min. It was kept at 550 °C for 2 h, and then taken out after natural cooling to obtain a zinc oxide nanofilm with a thickness of 3-6 μm.

6. The method for preparing a coated glass without color difference and with strong adhesion according to claim 5, characterized in that: The concentration of the borate metal salt in the borate metal hydrolysis solution is 30%, and the borate metal salt is chromium borate.

7. The method for preparing a coated glass without color difference and with strong adhesion according to claim 5, characterized in that: The molar ratio of zinc in the zinc oxide sol to non-boron metal ions in the borate metal hydrolysis solution is 5:

1.

8. The method for preparing a coated glass without color difference and with strong adhesion according to claim 5, characterized in that: The zinc oxide sol is prepared from zinc acetate as a raw material and polyvinyl alcohol with a molecular weight of 10,000 as an organic solvent, with a mass ratio of 1:10.

Citation Information

Patent Citations

  • Self-cleaning glass with strong adhesive force, and preparation method thereof

    CN112373134A